Pengembangan Sistem Pakar untuk Mendiagnosis Gangguan Perkembangan Anak dengan Metode Certainty Factor - Muhammad Zainudin Al Amin; Achmad Solichan; Aditya Putra Ramdani; Basirudin Ansor; Nova Christina Sari; Karima Elsami (Politeknik Kampar, 2024)
An expert system for diagnosing developmental disorders in children using the certainty factor method serves as a tool for early detection in children exhibiting unusual behavior for more than three months. Some common disorders in children include autism, oppositional defiant disorder (ODD), mental retardation, and ADHD (Attention Deficit Hyperactivity Disorder). The development of an expert system application for diagnosing developmental disorders in children using the certainty factor method was implemented using PHP and MySQL in the form of a website. Through this application, users can consult with the system as if consulting with an expert to identify the disorder affecting the child based on the symptoms experienced. The application also allows users to view medical records based on the examinations conducted.